Use of diatoms (Bacillariophyceae) for water quality assessment in two tropical streams in Costa Rica - Michels, Astrid (1998)
Effects of pig farm sewage water in two tropical streams were studied for a five month period considering physical chemical and biological parameters. The method of Lange-Bertalot and the method of Steinberg & Schiefele, both based on benthic diatoms, were applied for the biological water assessment. Results were compared to indices calculated from the physical chemical variables (oxygen, nitrate, nitrite, ammonia and phosphate). According to both methods the percentages of the diatom species groups reflected the increase: and subsequent decrease of pollution. However, in both methods, species groups did often not fit the criteria of the classification schemes for calculation of water quality. The sources of these problems were discussed in this paper. More information on the ecological requirements of diatoms in tropical areas is needed to design procedures for water quality assessment for tropical streams.